2017
DOI: 10.12799/jkachn.2017.28.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Non-suicidal Self Injury in Korean Adolescents

Abstract: Purpose: Non-Suicidal Self-Injury (NSSI), a highly prevalent behavior in adolescents, refers to the direct destruction of one's body tissue without suicidal intent. To date, the prevalence of adolescent self-injury in South Korea and its associated factors remain unknown. This study aims to determine the prevalence of self-injury in Korean adolescents as well as its associated factors. Methods: We assessed 717 middle school students by means of an anonymous self-report survey. Information about demographic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
2
15
1
Order By: Relevance
“…This finding is consistent with previous research, which indicate that PED visitation in youths was increasing and the largest increase was found in adolescents due SA or self-inflicted injury. 18 22 23 SA and NSSI have been reported to be prevalent in Korean children and adolescents, 10 11 12 24 25 and our study showed that more Korean youths are presenting to the PED for psychiatric problems, especially those relating to suicidality and NSSI. Considering these results together, the PED has a significant role in the acute management of high-risk psychiatric children and adolescents.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This finding is consistent with previous research, which indicate that PED visitation in youths was increasing and the largest increase was found in adolescents due SA or self-inflicted injury. 18 22 23 SA and NSSI have been reported to be prevalent in Korean children and adolescents, 10 11 12 24 25 and our study showed that more Korean youths are presenting to the PED for psychiatric problems, especially those relating to suicidality and NSSI. Considering these results together, the PED has a significant role in the acute management of high-risk psychiatric children and adolescents.…”
Section: Discussionsupporting
confidence: 56%
“… 2 7 8 9 Although little research on the prevalence of NSSI in the Korean population is present, NSSI is commonly observed among Korean adolescents with a prevalence of at least 8.8% to 9.2%. 10 11 12 SA and NSSI have a profound impact on families and communities and incur massive societal costs. 13 14 Hence, considerable clinical attention is warranted to develop preventive strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies conducted in Korea investigating self-injurious behavior in middle and high school students report varying degrees of lifetime prevalence, ranging from 8.8% to 22.8%; some studies find that the age of onset of self-injury is 12.4~13.8, which is similar to studies conducted overseas [ 9 , 10 , 11 , 12 , 13 ]. As a result of the Adolescent Personality and Mental Health Problems Screening Questionnaire conducted by the Korean Ministry of Education for all middle and high school students in Korea in 2018, the number of first-year middle school students who reported that they had engaged in self-harm was about 40,500/514,710 (7.9%), and about 30,000/514,710 (6.4%) in the first year of high school reported self-harm experiences [ 14 ].…”
Section: Introductionmentioning
confidence: 54%
“…The results of preceding research that insist affect regulation is the key function of self-injury and negative emotional states are the proximal risk factors of self-injurious behavior, indicate that further investigations should focus on negative emotion as a critical factor triggering self-injurious behavior. Many studies have identified depression as the risk factor predicting self-injurious behavior in Korea and abroad [ 10 , 11 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], and anxiety [ 10 , 39 , 40 ]. They are also strong proximal risk factors for self-injury [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 According to a recent systematic review of NSSI studies in Korea, which reviewed empirical studies conducted from 2000 to 2018, 14 depression and anxiety were reported as emotional factors predicting NSSI. [15][16][17][18][19] Negative urgency, defined as a tendency to act rashly when experiencing negative emotionality, was also suggested as predicting NSSI. 20 In addition, anger has been shown to significantly increase the frequency of the NSSI, which was more prevalent among women compared to men.…”
Section: Introductionmentioning
confidence: 99%